Information content of female copulation calls in wild long-tailed macaques (Macaca fascicularis) - Engelhardt, Antje (Springer-Verlag, 2011)
Primates are unusual in that many females display sexual signals, such as sex skin swellings/colorations and copulation calls, without any sex role reversal. The adaptive function of these signals remains largely unclear, although it has been suggested that they provide males with information on female reproductive status. For sex skin swellings, there is increasing evidence that they represent a graded signal indicating the probability of ovulation. Data on the functional significance of copulation calls are much scarcer. To clarify the information content of such calls, we recorded copulation calls in wild long-tailed macaques (Macaca fascicularis) and analysed the structure of these calls during the ovarian cycle. Specifically, we correlated selected call parameters with the female oestrogen to progestogen ratio (obtained from faecal samples), which are known to be elevated during the female's fertile phase. In addition, we ran a general linear mixed model for these call parameters, testing factors (cycle phase, occurrence/absence of ejaculation, male dominance status, occurrence/absence of mate guarding) which potentially influence female copulation calls in primates. Our results show that copulation calls of female long-tailed macaques signal mating outcome and rank of the mating partner, but not female reproductive status. They also show for the first time on primates that copulation calls can convey information on whether a female is mate guarded or not. We suspect that the function of these calls is manipulation of male mating and mate-guarding behaviour and that in this way the degree of sperm competition and ultimately male reproductive success is influenced.